CASH FLOW RATIO ANALYSIS TO ASSESS FINANCIAL PERFORMANCE - Baihaqi Ammy (Proceeding International Seminar of Islamic Studies, 2022)
This study describes the cash flow ratio to measure the financial performance of PT. Jaya Beton Indonesia. The author uses secondary data in the form of financial statements from 2010-2014. The research approach used is a quantitative descriptive approach, namely data in the form of numbers that are processed using certain calculation methods so as to provide a clear picture of the problems that have to do with cash flow ratios. The ratios used are Operating Cash Flow Ratio (AKO), Cash Coverage Ratio to Current Debt (CKHL), Capital Expenditure Ratio (PM), and Total Debt Ratio (TH). From the results of research on financial performance, the Operating Cash Flow Ratio (AKO) in 2012-2014 was below one, which means that there is a possibility that the company will not be able to pay its current liabilities. In the Capital Expenditure Ratio (PM) if it is lower, it indicates the low ability of operating cash flows to finance capital expenditures. And the ratio of Total Debt (TH) if the lower indicates the company has a capability that is less than the normal operating activities of the company.Keywords: Financial performance, Cash Flow Ratio.